Struktur dan Fungsi Pantun Managua pada Upacara Pernikahan di Koto Baru Kecamatan Rao Utara Kabupaten Pasaman - Asmal, Asmal; Gani, Erizal; Abdurahman, Abdurahman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was to describe the structure, function, and educational values ​​contained in the poem managua on wedding ceremony in New Koto Pasaman District of North Rao. The data of this study is the structure, functions, and values ​​education in managua rhyme. The data source of this research is the primary source of oral sources as spoken directly by the original speaker. Data collected using methods and techniques refer to record and advanced engineering techniques noted as descriptive method. The study's findings are managua rhyme structure consists of the physical structure and inner structure, function managua poem consists of eight of the ten functions rhymes Minangkabau, and educational values ​​managua poem consists of religious education and moral values​.